2020
DOI: 10.14807/ijmp.v11i6.1122
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hope and psychological well-being among male and female students of Farhangian University of Zanjan province

Abstract: The purpose of this study was to determine the relationship between hope and psychological well-being among the students of Farhangian University using a descriptive correlational research method. All students of Farhangian University of Zanjan province in the academic year of 2018-19 were considered and 324 of them were selected as the research sample. Hope scale Schneider (1991) and psychological well-being scale of Ryff (1989) were used as research tools. using SPSS 21 software, Pearson correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The results of the present study are in line with those reported by Hayes et al (2017), Ahmadi and Ramazani (2020), Sarker et al (2022), Tee et al (2022), since, though weak, a statistically significant linear correlation was found between hope and health.…”
Section: Mental Health and Hopesupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are in line with those reported by Hayes et al (2017), Ahmadi and Ramazani (2020), Sarker et al (2022), Tee et al (2022), since, though weak, a statistically significant linear correlation was found between hope and health.…”
Section: Mental Health and Hopesupporting
confidence: 93%
“…On the other hand, research has shown that even though hope can be defined/conceptualized and, consequently, measured in different ways, it effectively buffers against psychopathology/negative (mental health) outcomes, has a key role in recovery from mental illness, and is a robust correlate/predictor of several positive outcomes across various populations, cultures and countries, making it a protective resilience factor (e.g., Acharya & Agius, 2017;Ahmadi & Ramazani, 2020;Antunes et al, 2023;Ding et al, 2021;Feldman et al, 2023;Hayes et al, 2017;Laranjeira & Querido, 2022;Olsman, 2020;Park & Chen, 2016;Rustøen, 2021;Senger, 2023;Sarker et al, 2022;Snyder, 2002;Su et al, 2023;Tee et al, 2022).…”
Section: Hope and Mental Healthmentioning
confidence: 99%
“…On the other hand, research has shown that even though hope can be defined/ conceptualized and, consequently, measured in different ways, it effectively buffers against psychopathology/negative (mental health) outcomes, has a key role in recovery from mental illness and is a robust correlate/predictor of several positive outcomes across various populations, cultures and countries, making it a protective resilience factor (e.g., Acharya and [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Hope and Mental Healthmentioning
confidence: 99%